Extraction of Pectin from Banana Peels (Musa Paradiasica Fomatypica) for Biodegradable Plastic Films. (February 2019) - Chodijah, S.; Husaini, A.; Zaman, M; Hilwatulisan,
Abstract: The main goal of this research is to determine the effect of banana peels pectin on the characteristics of biodegradable film plastic, especially thickness, water resistance, tensile strength, and elongation. With the addition of citric acid, extract of banana peel starch as filler, and glycerol as plasticizer. The results showed that the use of citric acid could reduce the browning effect of pectin with the characteristics of water content of 11.56%, ash content of 3.060%, low methoxyl content of 3.906% (<7%), characteristics of the best biodegradable plastic film on the addition of pectin 5 grams with thickness characteristics 0.00387 cm, water resistance 63.63%, tensile strength of 10.5620 MPa, and elongation of 58.33%.